LEGAL PROTECTION OF NIKE TRADEMARK HOLDERS (STUDY IN KLITHIKAN MARKET OF YOGYAKARTA) - Doni Prasetio; Ani Yunita (RechtIdee, 2023)
Legal protection for Nike trademark holders in the Klithikan Pakuncen market in Yogyakarta is still not effective because there is no special regulation to protect Nike trademark holders. Law Number 20 of 2016 concerning Marks and Geographical Indications only concerns the protection of counterfeit goods. This research aims to determine the legal protection for the holder of the Nike trademark on counterfeit shoes in the Klithikan Pakuncen market in Yogyakarta. This study uses a type of combined legal research (normative-empirical) with a legal approach to examine the laws and regulations governing the legal protection of Nike trademark holders on counterfeit shoes circulating in the Klithikan Pakuncen Market, Yogyakarta. The study results concluded that legal protection for holders of counterfeit shoes at the Klithikan Pakuncen Market in Yogyakarta was not effective because the Ministry of Law and Human Rights and the Department of Industry and Commerce had not fully supervised, fostered, nor taken action. Brand infringement which is a complaint offense means that there is not yet complete extra supervision from brand owners to file complaints to parties such as the Ministry of Law and Human Rights and the Department of Industry and Commerce, which should enforce the law instead of doing it passively.